Relationship Between Mother's History of Preeclampsia and the Incidence of Stunting in Toddlers in the Work Area of Pekauman Public Health Center Banjarmasin - Teddyansyah, Teddyansyah; Ariani, Malisa; Latifah , Latifah (Universitas Ibn Khaldun Bogor, 2025)
Stunting is a chronic malnutrition condition whose prevalence has not yet reached the national target of 14%. The incidence of stunting in Indonesia still needs to be reduced according to the government's target. A history of preeclampsia is suspected as a risk factor for stunting so it needs to be studied. The purpose of this study was to determine the relationship between a history of preeclampsia in mothers and the incidence of stunting in toddlers. This study is a quantitative study with an analytical survey design and a cross- sectional approach in 30 mothers and children aged 24-59 months at the Pekauman Health Center who were selected using a purposive sampling technique. The research data were collected using observation sheets and anthropometric examinations and analyzed using the chi square test. The results showed that most mothers were in the non-risk age category (66.7%), most children were in the toddler age category (63.3%), and the percentage of boys and girls was balanced (50%). Most mothers had a history of preeclampsia (70%) and most children had stunting status (60%). The results of the chi square test showed a p value = 0.006. Adequate nutritional intake is needed for children to improve nutritional status.